1990
DOI: 10.1080/17450399009421078
|View full text |Cite
|
Sign up to set email alerts
|

Sites of Digestion in Beef Steers Fed Bermudagrass Hay and Supplemented with High-Nitrogen Feeds alone or Mixed with Tallow

Abstract: Five crossbred beef steers (329 kg) were used in a 5 x 5 Latin square experiment with 14-d periods to determine the effects of supplementation with high-nitrogen (N) feeds alone or mixed with tallow on sites of digestion with a basal diet of bermudagrass hay. Hay was 1.93% nitrogen, 75% neutral detergent fibre and fed at 1.83% of body weight (dry matter; DM). Supplements were basal (B; 105 g DM): 81.8% dried molasses product (DMP) and 18.2% calcium carbonate (CC); soybean meal (S; 942 g DM): 88.0% soybean meal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1990
1990
1993
1993

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…S LWG was slightly lower than for other Ruminal losses of N for S, GB and M + S were considerable, whereas for other treatments N intake and duodenal flow differed little. N intake and appearance at the duodenum have been similar in other trials with unsupplemented cattle fed bermudagrass (Jones, Goetsch, Stokes and Colberg, 1988;Landis et al, 1989;Hall, Goetsch, Landis, Forster and Brake, 1990). The ruminal loss of N for treatment GB in this study could have been due to the feeding of the supplement once instead of twice per day as indicated by the work of Landis et al (1989).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…S LWG was slightly lower than for other Ruminal losses of N for S, GB and M + S were considerable, whereas for other treatments N intake and duodenal flow differed little. N intake and appearance at the duodenum have been similar in other trials with unsupplemented cattle fed bermudagrass (Jones, Goetsch, Stokes and Colberg, 1988;Landis et al, 1989;Hall, Goetsch, Landis, Forster and Brake, 1990). The ruminal loss of N for treatment GB in this study could have been due to the feeding of the supplement once instead of twice per day as indicated by the work of Landis et al (1989).…”
Section: Discussionsupporting
confidence: 71%
“…In period 1, and pattern of energy liberation from LWG was highest for M + GB, while M + bermudagrass fermentation. The ruminal loss of N for treatment GB in this study could have been due to the feeding of the supplement once instead of twice per day as indicated by the work of Landis et al (1989). Landis, Goetsch, Forster and Brake (1989) also increased ruminal N loss by supplementing beef steers consuming bermudagrass hay with soya-bean meal, but pre-intestinal N disappearance was not markedly affected by providing a mixed maize-gluten-blood meal supplement.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Numbers of protozoa in the rumen were not estimated, but increases are frequently associated with elevated butyrate production (Ushida et al, 1986), as was observed with corn supplementation in this experiment. Supplementing forage diets with corn has increased the number of protozoa (Hall et al, 1990;Landis et al, 1990), and legumes promote relatively large protozoal populations (Ushida et al, 1986;Ushida and Jouany, 1990). Constant feed intake, restricting ruminai digesta outflow with supplementation, and minimizing protozoal washout (Michalowaski and Muszynski, 1978), could have accentuated substrate-induced increases in numbers of protozoa (Jouany et al, 1988).…”
Section: Ruminai Digesta Characeristics -Vfamentioning
confidence: 97%
“…The manner of delivery of fat to the animalas a fat supplement (Ikwuegbu and Sutton 1982;Broudiscou et al 1990;Landis et al 1990), as supplementation with a fat-containing product (Davenport et al 1987), or as a fatcoated supplement (Glenn et al 1977) affects the degradability of feed nutrients.…”
mentioning
confidence: 99%